2009
DOI: 10.1124/dmd.108.024836
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Apical Localization of Abcc2/Mrp2 and Phosphorylation Status of Ezrin in Rat Intestine

Abstract: ABSTRACT:The multidrug resistance-associated protein 2/ATP-binding cassette transporter family C2 (Mrp2/Abcc2) is an ATP-dependent export pump that mediates the transport of a variety of organic anions. Abcc2 is mainly expressed on the canalicular membrane of hepatocytes and also the brush-border membrane of intestinal epithelial cells. We have previously reported that Abcc2 is rapidly internalized from the canalicular membrane during acute oxidative stress, which induces protein kinase C (PKC) activation in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…44) Accordingly, whether certain membrane proteins decide which to choose out of the ERM as each partner for their plasma membrane localization may be dependent on the kinds of tissues and/or membrane protein itself. 6,45,[48][49][50]52) It also remains to be determined what increases in the amount of both radixin and P-gp bound to PI(4,5) P2 means under our experimental condition. Because of increases in the both protein expressions of the input as shown in our previously study, 6) it may be merely due to that contact probability of P-gp and radixin could be simply elevated, which may in turn magnifies the number of molecular complex at the small intestinal membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44) Accordingly, whether certain membrane proteins decide which to choose out of the ERM as each partner for their plasma membrane localization may be dependent on the kinds of tissues and/or membrane protein itself. 6,45,[48][49][50]52) It also remains to be determined what increases in the amount of both radixin and P-gp bound to PI(4,5) P2 means under our experimental condition. Because of increases in the both protein expressions of the input as shown in our previously study, 6) it may be merely due to that contact probability of P-gp and radixin could be simply elevated, which may in turn magnifies the number of molecular complex at the small intestinal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have clearly demonstrated that PtdIns(4,5) P2 is a critical factor for promoting the dissociation of ERM, 22,25,26) which enables ERM translocation to the plasma membrane where the ERM proteins can interact with various membrane proteins. [44][45][46][47][48][49] Moreover, we recently demonstrated the existence of molecular interactions between P-gp and each of the ERM proteins in the small intestinal membrane by immunoprecipitation analysis using an anti-P-gp antibody.…”
Section: Discussionmentioning
confidence: 99%
“…4,14,20) As is well documented using histological methods, ezrin or moesin are mainly localized on the epithelial cells of villi surfaces or the endothelial cells of the sub-epithelial capillaries, respectively. 28,29,40) In contrast, radixin has been shown to be widely distributed in the epithelial and/or endothelial cells of the small intestine as indicated by immunofluorescence analyses. 12,29) In recent years, some researchers have proposed that radixin functions as a scaffold protein for P-gp and other membrane transporters not only in the canalicular membrane of the hepatocytes, 14,20) but also in the small intestine, similarly to ezrin.…”
Section: Discussionmentioning
confidence: 99%
“…12) Ezrin is expressed in the epithelium, 12,18,29) and is the only ERM protein that has been proven to interact with P-gp by use of immunoprecipitation analysis. 28) On the other hand, radixin is expressed in the liver 14,17,20,31) and kidney, 29) as well as in the epithelium of the small intestine, 32) although not to the extent of ezrin. 18,29) Furthermore, radixin has been just recently proposed to play a crucial role in regulating the membrane localization and functional activity of P-gp in the small intestinal by using mice lacking radixin.…”
mentioning
confidence: 99%
See 1 more Smart Citation